Search for CP violation in D0→π−π+π0 decays with the energy test - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Physics letters, 2015)
A search for time-integrated CP violation in the Cabibbo-suppressed decay D0→π−π+π0 is performed using for the first time an unbinned model-independent technique known as the energy test. Using proton-proton collision data, corresponding to an integrated luminosity of 2.0 fb−1 collected by the LHCb detector at a centre-of-mass energy of s=8 TeV, the world's best sensitivity to CP violation in this decay is obtained. The data are found to be consistent with the hypothesis of CP symmetry with a p-value of (2.6±0.5)%.